Aerodynamic analysis of mathematically modelled propeller for small UAV using CFD in different temperature conditions - Ganesan, Tamilselvan (Strojniški vestnik, 2023)
Unmanned aerial vehicle (UAV) usage has witnessed a significant rise owing to its cost-effectiveness and versatile applications. However, the design techniques for UAV propellers, encompassing aerodynamic and structural analysis, have received limited attention from researchers. A well-designed propeller can effectively reduce battery consumption and enhance overall efficiency. This study focuses on mathematically designed propellers and compares them with advanced precision composite (APC) Slow Flyer propeller blades in terms of thrust coefficients, power coefficients, and efficiency. The investigation includes the utilization of tetrahedron meshing in simulations, employing the standard k–? (k–omega) model. To evaluate the accuracy of the blade element theory (BET) in predicting thrust, the simulation data is compared with BET results. Furthermore, the study encompasses experimental testing to validate the simulation findings. The findings demonstrate that the mathematically modelled propeller outperforms the APC Slow Flyer propeller across all ranges of revolutions per minute (rpm). When comparing the results of both methods, BET exhibits an error difference of 10 % in higher rpm ranges, but this error diminishes as the rpm decreases. This study contributes a novel design technique for modelling propellers using mathematical formulas and provides a comprehensive comparison of their aerodynamic properties with existing propellers, utilizing both BET and computational fluid dynamics (CFD) methods, along with experimental validation.
Keywords: blade element theory; brezpilotna zračna plovila; computational fluid dynamics; matematično načrtovanje; mathematical design; propelerji; propellers; računalniška dinamika tekočin; teorija lopatic; unmanned aerial vehicles